PERANAN PEMERINTAH DALAM TATA KELOLA PASAR MALAM BERDASARKAN PERATURAN DAERAH KOTA SAMARINDA NOMOR 13 TAHUN 2011 TENTANG RETRIBUSI JASA UMUM - Novi Yanti Sari (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT          This study, entitled “The Role of Government Governance Night Market Based Samarinda City Regional Regulation No. 13 of 2011 Concerning Public service levies”.          This study aims to determine the role of the government of Samarinda in Managing the Night Market in the city of Samarinda and to know how to maximize the regional revenue through levies on the Market Night Market.          This research was conducted in the Office of the City Market Samarinda to conduct interviews with the Head of Revenue and retrieve the data that is relevant in the market especially regarding levies Night Market. In addition, the study also conducted a study of literature by way of examining the books, literature and laws and regulations relating to the issues that will be discussed in the thesis writer.          The findings obtained from this study include: (1) the absence of local regulations that specifically govern the management of the night market in Kota Samarinda. (2) The efforts made by the Office of Market Management Samarinda to obtain retribution from the market from traders who sold the night market, among others by direct observation on the location of the night market so as to obtain the data to develop a night market. In addition the market management office asking for the enactment of local legislation new regional regulations in order to provide facilities such as proper infrastructure specific to the merchant who sold the night market. To do so, the levy charged to the merchant who sold the night market, ultimately achieved balanced development of both government and society, especially the night market traders. Keywords: Governance Night Market, Regulation No. 13 In 2011.